2012
DOI: 10.1002/ppap.201100168
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Dominant Reactions for Ethylene Destruction in Non‐Thermal Atmospheric Plasmas

Abstract: A crucial step, which is still not well understood in the destruction of volatile organic compounds (VOCs) with low temperature plasmas, is the initiation of the process. Here, we present a kinetic model for the destruction of ethylene in low temperature plasmas that allows us to calculate the relative importance of all plasma species and their related reactions. Modifying the ethylene concentration and/or the SED had a major impact on the relative importance of the radicals (i.e., mainly atomic oxygen) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…In the plasma gas phase reactions, acetone molecules can be destroyed by energetic electrons to form acetone radicals (e.g., CH 3 COCH 2 • ), methyl radicals (CH 3 • ) and acetyl radicals (CH 3 CO • ) via H-abstraction and C-C bond rupture. Previous experimental and modelling studies have shown the importance of metastable N 2 and atomic oxygen in the destruction of gas pollutants in air plasmas [34][35][36], which suggests the contribution of these species to acetone destruction cannot be ruled out. The oxidation of the aforementioned by-products and intermediates to final products such as CO 2 and water are likely to happen in an oxidative plasma environment.…”
Section: Plasma-catalytic Oxidation Of Acetonementioning
confidence: 98%
“…In the plasma gas phase reactions, acetone molecules can be destroyed by energetic electrons to form acetone radicals (e.g., CH 3 COCH 2 • ), methyl radicals (CH 3 • ) and acetyl radicals (CH 3 CO • ) via H-abstraction and C-C bond rupture. Previous experimental and modelling studies have shown the importance of metastable N 2 and atomic oxygen in the destruction of gas pollutants in air plasmas [34][35][36], which suggests the contribution of these species to acetone destruction cannot be ruled out. The oxidation of the aforementioned by-products and intermediates to final products such as CO 2 and water are likely to happen in an oxidative plasma environment.…”
Section: Plasma-catalytic Oxidation Of Acetonementioning
confidence: 98%
“…In such a plasma, the initially generated electrons collide with the gas molecules to produce chemically reactive species including free radicals, excited atoms, ions and molecules [7,8]. Both highly energetic electrons and reactive species play important roles in the initiation and propagation of a variety of physical and chemical reactions in low temperature plasma processes [9].…”
Section: Introductionmentioning
confidence: 99%
“…NTP generated by the dielectric barrier discharge reactor consisted of numerous micro-discharges in the plasma region. The number of micro-discharges in each discharge period was increased at a higher SED with fixed gas flow rate, which creates more reaction channels for the decomposition of H 2 S and intermediates, resulting in the enhanced removal of H 2 S [35][36][37]. It is worth noting that no ozone was detected in this work, which might be consumed by local heating, catalytic effect, or plasma oxidation reactions [38].…”
Section: Plasma-catalytic Oxidation Of H 2 Smentioning
confidence: 92%